Effects of self-monitoring of heart rate and additional sprint running on exercise intensity and technical performance during small-sided games in soccer - Swinton, P. A.; Munro, H.; Dolan, E.; Burgess, K. (Journal of Trainology, 2016)
Objectives: The purpose of this study was to assess whether relatively simple interventions including self monitoring of heart rate and the use of targeted sprints for those with the lowest relative HR values (%HRmax) could be used to increase exercise inten sity during small sided games (SSGs) in soccer. A secondary aim of the study was to assess the effect of these interventions on overall gameplay. Design and Methods: Fourteen male semi-professional players performed SSGs (6 vs. 6) under four conditions including a control, a self-monitoring approach where players monitored their own HR via a wristwatch, and two sprint conditions where players with HR values below 90%HRmax performed sprints either during the game or during the recovery period between games. A linear mixed effects model was used to test for main effects whilst accounting for covariances between observations made on the same player. Results: The results identified relatively small but significant differences in average %HRmax (p < 0.001) and RPE values (p < 0.001) between the three modified conditions and the control. No significant differences were found between any of the modified conditions for measures of exercise intensity. On average, the modified conditions resulted in a 3.7% increase in %HRmax values and a 9.3% increase in RPE. Conclusion: The results from this study demonstrate that exercise intensity of SSGs in soccer can be increased by relatively simple and practical manipulations, the most basic of which requires only the use of inexpensive HR monitors.